Transsexual law: the transsexual rights in Malaysia and the United Kingdom / Aliah Mohamad Asri, Ibtisam Syukriah Japri and Noor Asyima Shuaib - Mohamad Asri, Aliah; Japri, Ibtisam Syukriah; Shuaib, Noor Asyima (2009)
This research paper was conducted to compare between Malaysia's and United Kingdom's transsexual law. This research will also looked into the applicability of adopting United Kingdom's in filling the lacuna in the law of Malaysia regarding the issue of transsexual. At first instance, Article 5 is likely to used to govern the rights to change gender on the basis of fundamental liberties. However, this is not likely because Article 5 is too broad and does not even touch on the issue of gender recognition. In the light of the above mentioned facts, we made the United Kingdoms legislation as a guideline in the process of proposing the law to be legislated in Malaysia. However, the applicability of the United Kingdom's legislation in Malaysia is limited as our country is mainly inhabited by Muslims. There are several recommendations to be adopted to improve the practicability of such law in Malaysia.